A One‐step Fluorescence Sensor Based on Molybdenum Disulfide Nanosheets for the Detection of Potassium Ions. Issue 1 (21st November 2022) - He, Shiliang; Fan, Taojian; Zhang, Yingjie; Wei, Chenxi; Chen, Zhuolang; Shi, Yao; Hu, Junqing
Abstract: Determination of potassium ion concentration in biological samples is of great significance due to its vital role in the maintenance of physiological activities. Single or few‐layered transition metal dichalcogenides (TMD, e. g., MoS2, WS2, TiS2 ) have recently found wide applications in optoelectronics and biomedical engineering. Herein, for the first time, MoS2 nanosheets were integrated with G‐quadraplex DNA secondary structures to construct a fluorescence sensor for detecting potassium ions. The biosensor showed merits such as ease of preparation, ease of use, low‐cost, broad linear working range, as well as sufficient sensitivity, specificity and practical applicability, demonstrating its promise as an effective potassium ion sensor for practical applications. To the best of our knowledge, this is the first report on the combination of TMD nanomaterials and DNA quadraplex for the development of nanodevices. The proposed TMD nanosheets‐G‐quadraplex sensing formulation could enable the devise of other nanomachines and nanosensors considering the versatility of TMD nanomaterials and G‐quadraplex‐containing aptamers. Abstract : MoS2 nanosheets were integrated with G‐quadraplex DNA secondary structures to construct a fluorescence sensor for detecting potassium ions. The biosensor showed merits such as easy‐to‐prepare, ease‐of‐use, low cost, broad linear working range, as well as sufficient sensitivity, specificity and practical applicability.